The Patterns of Restriction Fragment of Several Enzymes to Distinguish Toxoplasma gondii Isolates Virulent and Avirulent Strains using GRA1 and GRA7 Genetic Marker - Fitrine Ekawasti; Eko Setyo Purwanto; Farlin Nepho; Dyah Ayu Kurniawati; Didik Tulus Subekti; Rini Damayanti; Siti Sa’diah; Umi Cahyaningsih (Bogor Agricultural University, Indonesia, 2023)
Toxoplasma gondii pathogenicity depends on the type derived from a clonal population. A genetic analysis of the locus has been carried out to determine the different genotypes of T. gondii (strain types I, II, and III) that are associated with human toxoplasmosis. The several genotypes of T. gondii (strain types I, II, and III) that are linked to human toxoplasmosis have been identified through genetic study of the locus. In this investigation, PCR-RFLP was found to be a useful, and simple method genotypic characterization. The objective of this study was to genotyping characterize T. gondii RH and BEV strains isolates by PCR-RFLP using several restriction enzymes. T. gondii tachyzoite DNA was extracted and amplified by PCR using dense granule genetic markers (GRA1 and GRA7) designed with Primer3plus. The amplification were digested using the restriction enzymes. The PCR-RFLP amplified dense granule products was used to classify strains into two genotypes of T. gondii (virulent and avirulent). The results demonstrated that the RFLP patterns of the GRA1 and GRA7 gene area digested by DdeI, MvaI, HinfI, RsaI, and Sau96I enzymes can be used to identify virulent or avirulent strains of T. gondii. Toxoplasma gondii RH and BEV strain produced different digestion product which can be used to distinguished the strains.